1999
DOI: 10.1002/(sici)1097-4628(19990404)71:14<2385::aid-app10>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Application of poly(phthalazinone ether sulfone ketone)s to gas membrane separation

Abstract: A series of poly(phthalazinone ether sulfone ketone) (PPESK) copolymers containing different component ratios of bis(4-fluorodiphenyl) ketone and bis(4-chlorodiphenyl)sulfone with respect to a certain amount of 4-(4-hydroxyphenyl)-2,3-phthalazin-1-one were synthesized by polycondensation. Glass transition temperatures of these polymers were adjusted from 263°C to 305°C by changing the ratios of reactants. Gas permeability and selectivity of the dense membranes of the polymers for three kinds of gases (CO 2 , O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Novel poly(phthalazinone ether sulfone ketone) (PPESK) copolymers containing different ratios of diphenylsulfone and diphenylketone units were previously synthesized [2][3][4] from 1,2-dihydro-4-(4-hydroxy-phenyl)-phthalazin-1-one [5,6] . There are plans to commercialize these condensation polymers, derived from this phthalazinone monomer that is readily prepared from the commodity chemicals phenol, phthalic anhydride and hydrazine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel poly(phthalazinone ether sulfone ketone) (PPESK) copolymers containing different ratios of diphenylsulfone and diphenylketone units were previously synthesized [2][3][4] from 1,2-dihydro-4-(4-hydroxy-phenyl)-phthalazin-1-one [5,6] . There are plans to commercialize these condensation polymers, derived from this phthalazinone monomer that is readily prepared from the commodity chemicals phenol, phthalic anhydride and hydrazine.…”
Section: Introductionmentioning
confidence: 99%
“…So it can be used as a substitute for materials in numerous engineering applications. In addition, membranes made from PPESK have shown good separation and permeation properties for both gas and liquid separations [4,7] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition phthalazinone and its derivatives were bisphenol-like monomers which can be polymerized with the activated aryl dihalide monomers to give amorphous polymers [23] with high glass transition temperature and excellent thermo-stability, which are soluble in common organic solvents [23,24]. Recently [25][26][27] a series of poly(phthalazinone ether sulfone ketone(PPESK)) copolymers used as potential polymer in proton exchange membrane fuel cells [PEMFCs]. Corrosion of metals is a major industrial problem that has attracted many investgation and researchers [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to develop high-temperature resistant and chemical stability membrane materials. Poly(phthalazine ether sulfone ketone) (PPESK) is a novel polymer, which was synthesized by Xigao Jian et al [2]. And the polymer contains rigid aromatic rings and shows superior mechanical strength, chemical resistance and very high glass transition temperature (Tg) [3].…”
Section: Introductionmentioning
confidence: 99%
“…It could be concluded from the polymer's properties that the polymer has potential for longer life and lower capital cost membrane preparation. It was also demonstrated that PPESK is a potential membrane material for UF [4] and high temperature gas separation [2].…”
Section: Introductionmentioning
confidence: 99%